TIPE KEPEMIMPINAN KEPALA SEKOLAH DALAM PENDIDIKAN ISLAM - Sukatin; Muammar Qadafi; Inda Salsabila; Sindy Septia Bella; Feni Angaria; Riski Firmansyah (Jurnal Studi Islam Lintas Negara (Journal of Cross-Border Islamic Studies), 2022)
A leader is essentially someone who has the ability to influence the behavior of others in their work by using power. It is in his activities that the leader has the power to direct and influence his subordinates in relation to the tasks that must be carried out. Principal leadership types in general are personal leadership types, non-personal leadership types, authoritarian leadership types, democratic leadership types, paternalistic leadership types, leadership types according to talent. The leader's duties in his leadership include; exploring the needs of the school community he leads, from that desire he can pick realistic and achievable desires, convince his subordinates about what they want, which is realistic and which is actually imaginary. A professional leader is a leader who understands his duties and obligations, and is able to establish a good cooperative relationship with his subordinates, so as to create a work atmosphere that makes subordinates feel safe, secure, and have the freedom to develop their ideas in order to achieve the goals that have been set